Sports economics - Blair, Roger D., (Cambridge University Press, 2012)
Sports Economics, the most comprehensive textbook in the field by celebrated economist Roger D. Blair, focuses primarily on the business and economics aspects of major professional sports and the NCAA. It employs the basic principles of economics to address issues such as the organization of leagues, pricing, advertising and broadcasting as well as the labor market in sports. Among its novel features is the candid coverage of the image and integrity of players, teams, managers and the leagues themselves, including cases of gambling, cheating, misconduct and steroids. Blair explains how economic decisions are made under conditions of uncertainty using the well-known expected utility model and makes extensive use of present value concepts to analyze investment decisions. Numerous examples are drawn from the daily press. The text offers ample boxes to illustrate sports themes, as well as extensive use of diagrams, tables, problem sets and research questions.